North China Plain threatened by deadly heatwaves due to climate change and irrigation - Suchul Kang (Nature Portfolio, 2018)
Irrigation increases the intensity of heatwaves over the North China Plain but how this will be exacerbated by climate change has not been quantified. Here the authors show that irrigation enhances magnitude of extreme wet-bulb temperature and intensity of heatwaves in this region.